2015
DOI: 10.14740/cr384w
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Reduce Heart Failure Readmissions and Inpatient Costs

Abstract: BackgroundThe objective of this study was to evaluate the effect of a disease management intervention on rehospitalization rates in hospitalized heart failure (HF) patients.MethodsPatients treated with the TEACH-HF intervention that included Teaching and Education, prompt follow-up Appointments, Consultation for support services, and Home follow-up phone calls (TEACH-HF) from January 2010 to January 2012 constituted the intervention group (n = 548). Patients treated from January 2007 to January 2008 constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Our data trends were similar to the effects found in the TEACH-HF trial 24. Also, this study demonstrates the importance of prospective validation of statistically derived metrics, in order to translate statistical derivations into real-world effects.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our data trends were similar to the effects found in the TEACH-HF trial 24. Also, this study demonstrates the importance of prospective validation of statistically derived metrics, in order to translate statistical derivations into real-world effects.…”
Section: Discussionsupporting
confidence: 80%
“…Prior studies on this topic have shown that proven strategies to reduce readmissions involve a combination of education and organised outpatient follow-up 24. This supports the notion that exacerbation of HF starts up to 2 weeks prior to hospitalisation, suggesting that close outpatient monitoring and intervention can stabilise patients prior to the need for hospitalisation 10 25…”
Section: Discussionsupporting
confidence: 54%
“…26 The study nurse used the “teach-back” method to ensure patient understanding. 27,28 The predischarge education also included a demonstration of how to use the remote home telemonitoring equipment and an explanation of why monitoring physiological variables is important for patients.…”
Section: Methodsmentioning
confidence: 99%
“…The teachback method is not a test of a person's knowledge; it is a way to explore how well the messages are delivered and what needs to be clarified (Agency for Healthcare Research and Quality, 2015). This method has been used to significantly improve patient satisfaction (Kelly & Putney, 2015), knowledge retention (White, Garbez, Carroll, Brinker, & Howie-Esquivel, 2013), and reduce hospital readmissions (Howie-Esquivel et al, 2015). A recent systematic review found 10 studies that used the teach-back method to deliver self-management education to patients with various chronic diseases.…”
Section: Literature Reviewmentioning
confidence: 99%